Memperkenalkan dan Mempraktikan Booklet Resep Pemanfaatan Bahan Pangan Lokal untuk Mencegah Stunting dengan Nama Formula Sehat di Desa Kainbaun - Fitriyaningsih, Fitriyaningsih; Panjaitan, Tiolina Klara; Simanihuruk, Ramatian; Simbolon, Romida (Universitas Pahlawan Tuanku Tambusai, 2026)
Stunting remains one of the major nutritional problems in Indonesia, particularly in rural areas. Efforts to prevent stunting need to be carried out through nutrition education and the utilization of local food resources available in the community. This study/community service aims to introduce and implement the Formula Sehat Recipe Booklet as a nutrition education medium based on local food in Kainbaun Village. The methods used include socialization, cooking demonstrations, and family assistance in processing local food ingredients into balanced nutritious menus. The booklet contains simple recipes with adequate protein, vitamins, and minerals tailored to the needs of children and pregnant women. The results of the activity showed an increase in community knowledge regarding the importance of balanced nutrition, as well as skills in processing local food into healthy meals. Thus, Formula Sehat through this recipe booklet is expected to serve as a practical and sustainable strategy to prevent stunting in Kainbaun Village.